Effect of applying head-shaking maneuver before Epley maneuver in BPPV - Bulğurcu,Suphi (2022)
Abstract Introduction: The Epley maneuver is applied in the treatment of benign paroxysmal positional vertigo, the BPPV. However, dizziness and balance problems do not improve immediately after the treatment. Objective: In this study, the effectiveness of the head-shaking maneuver before the Epley maneuver was investigated in the treatment of BPPV. Methods: Between March 2020 and August 2020, ninety-six patients with posterior semicircular canal BPPV were analyzed prospectively. The patients were divided into two groups: patients who underwent the Epley maneuver only in the treatment (Group 1) and patients who underwent the Epley maneuver after the head-shaking maneuver (Group 2). The results of the Berg balance scale and dizziness handicap index were evaluated before the treatment and at the first week after the treatment. Results: The improvement in functional, emotional, and physical dizziness handicap index and Berg balance scale values after the treatment was found to be statistically significant in both groups. It was determined that the change in functional and physical dizziness handicap index and Berg balance scale values of the patients in Group 2 was statistically higher than those in Group 1. Although, the change in emotional dizziness handicap index values in Group 2 was higher than those in Group 1, no statistical significance was found between the groups. Conclusion: As a result of our hypothesis, we think that in the treatment of posterior semicircular canal BPPV, the otoliths adhered to the canal can be mobilized by the head-shaking maneuver, and this will contribute to the increase of the effectiveness of the Epley maneuver.